PHENOTYPIC FEATURES OF T REGULATORY CELLS IN EARLY RHEUMATOID ARTHRITIS - A. S. Avdeeva; Yu. P. Rubtsov; T. V. Popkova; D. T. Dyikanov; E. L. Nasonov (Научно-практическая ревматология, 2017)
Objective: to investigate the count and characteristics of the phenotype of T regulatory cells (Treg) in the peripheral blood of healthy donors and patients with early rheumatoid arthritis (RA), by using multicolor flow cytometry.Subjects and methods. The investigation enrolled 39 patients with early RA. The percentage and absolute count of Treg (FoxP3+CD25+, surface CD152+, intracellular CD152+, FoxP3+CD127, CD25+CD127, FoxP3+ICOS+, FoxP3+CD154+; and FoxP3+CD274+) was determined by multicolor flow-cytometry. A control group consisted of 20 healthy donors matched for sex and age with the examined patients.Results and discussion. In the patients included in the study, the median [25th; 75th percentiles] DAS28 was 5.01 [4.2; 5.8]; high, moderate, and low activity showed 22 (48.9%), 20 (44.4%), and 3 (6.7%) patients, respectively. The patients with early RA had a lower percentage of FoxP3+CD25+ cells and a lower percentage and absolute count of FoxP3+ICOS+, FoxP3+CD154+, and FoxP3+CD274+ T cells than the healthy donors (p<0.05 in all cases). There was a negative correlation of the percentage of FoxP3+CD25+ cells with C-reactive protein (CRP) (r = -0.4), that of intracellular CD152+ with DAS28 (r = -0.35), erythrocyte sedimentation rate (ESR) (r = -0.46), and CRP (r=-0.54); that of FoxP3+CD127 with CRP (r = -0.42); that of CD25+CD127 with DAS28 (r = -0.38), Simplified Disease Activity Index (r = -0.41), Clinical Disease Activity Index (r = -0.36), ESR (r = -0.39), and CRP (r = -0.47) (p < 0.05 in all cases).Conclusion. The findings suggest that the functional activity of Treg is impaired in early RA, which has an impact on the activity of the inflammatory process.